(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of the research is to substantiate the main parameters of the machine working elements for preparing the soil for sowing on the ridges and their mutual location. The authors have developed a machine that performs all technological operations to prepare the soil for sowing potatoes on the ridges in one pass in the field. The machine performs surface loosening of the soil, strip deep loosening of the soil, formation of ridges, loosening of the surface layer of the ridge top, compaction and giving them a trapezoidal shape in one pass. The design of the developed machine for realization of technology of preparation of soil for potatoes sowing is resulted. The basic principles and methods of classical mechanics, mathematical analysis and statistics were used in this study.